2022
DOI: 10.1097/hjh.0000000000003127
|View full text |Cite
|
Sign up to set email alerts
|

Influences of achieved SBP on age and sex-related left ventricular structural alteration in community hypertensive populations

Abstract: Objective: To evaluate age and sex-related left ventricular (LV) structural alteration in community hypertensive populations, and to explore whether achieved systolic blood pressure (SBP) (<120, < 130 and <140 mmHg) would modify the association between age and sex with LV structural alteration.Method: A total of 1419 community hypertensive people (mean age 61 years, women 50.5%) without cardiovascular disease and left ventricular hypertrophy (LVH) at baseline were included. LV structural measures were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
(75 reference statements)
1
2
0
Order By: Relevance
“…Beyond the HALP Score, our study identified female sex as a risk factor for LVH in older patients with hypertension. The findings align with those from a prospective study in 1419 patients with hypertension without initial LVH, which has highlighted that women have a greater risk of developing LVH than men [32]. Hoshida et al [33] have shown a more pronounced increase in LVH and myocardial stiffness in older female patients with hypertension than male patients.…”
Section: Discussionsupporting
confidence: 84%
“…Beyond the HALP Score, our study identified female sex as a risk factor for LVH in older patients with hypertension. The findings align with those from a prospective study in 1419 patients with hypertension without initial LVH, which has highlighted that women have a greater risk of developing LVH than men [32]. Hoshida et al [33] have shown a more pronounced increase in LVH and myocardial stiffness in older female patients with hypertension than male patients.…”
Section: Discussionsupporting
confidence: 84%
“… 14 Long-term hypertension consequences regarding LVH have also been detected, with hypertensive women having a higher risk for the development of LVH compared to men. 15 This association between the women population and LVM index alteration was not significant in the case of achieving systolic blood pressure <120 mmHg and <130 mmHg, providing a clear effect of hypertension despite age. 15 Furthermore, the pattern of hypertension plays an important role.…”
Section: Left Ventricular Hypertrophymentioning
confidence: 85%
“… 15 This association between the women population and LVM index alteration was not significant in the case of achieving systolic blood pressure <120 mmHg and <130 mmHg, providing a clear effect of hypertension despite age. 15 Furthermore, the pattern of hypertension plays an important role. Abnormalities and particularly an increase in circadian blood pressure variability seem to be associated with higher LV mass index.…”
Section: Left Ventricular Hypertrophymentioning
confidence: 85%